Growth Dynamics and Water Potential Components of Three Summer Squash (Cucurbita pepo L.) Cultivars - Alejo RODRÍGUEZ-BURGOS; Armando CARRILLO-LÓPEZ; Tomás OSUNA-ENCISO; Manuel BÁEZ-SAÑUDO; Adriana SAÑUDO-BARAJAS; Rosalba CONTRERAS-MARTÍNEZ; José de Jesús ZAZUETA-MORALES; Misael Odin VEGA-GARCÍA; Dolores MUY-RANGEL (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2015)
Summer squash fruit is a horticultural crop that possesses a very short postharvest life due to its high rates of metabolism and transpiration along with a low cuticle resistance exhibited mainly when the fruit is harvested at horticultural maturity. This research was realized following the fruit growth of the summer squash cultivars: ‘Enterprise’, ‘Pascola’ and ‘Hurakan F1’, whose seeds were germinated in polystyrene trays and their seedlings were subsequently transferred to pots for optimum growth under greenhouse conditions. Fruits were sampled at 3, 5, 7 and 9 days after anthesis (DAA).  Physical (weight, diameter, and length of fruit), chemical (pH, titratable acidity and total soluble solids), hydric status (water, osmotic and pressure potentials), and histological analysis were done. The highest number of fruits having marketing quality were shown in both ‘Pascola’ and ‘Hurakan F1’ cultivars at 7 DAA, whereas, in ‘Enterprise’ was shown at 9 DAA. Marketing quality fruits from the three cultivars showed similarities on pH (about 6.6), titratable acidity (TA) decreases in ‘Enterprise’ and ‘Hurakan F1’, whereas total soluble solids (TSS) decreases in ‘Pascola’ and ‘Hurakan F1’ (p≤ 0.5). From 3 to 9 DAA, in all cultivars, the water potential was close to -1.0 MPa, the osmotic potential showed an increasing pattern ranging between -1.59 and -1.15 MPa, and the pressure potential remained in the positive range. Tissue water stability was histologically related to a well-defined parenchyma tissue showing thin-walled, polygonal, intact and turgid cells during fruit growth.